Ms Excel Macro Aplications of Finite Differece and Integration Method for Simply Supported Rectangular Plates Under Sinusoidal Load - Savaş, Sedat (Fırat University, 2018)
In this study, the finite differences and the method of integration were compared to find displacements in an elastic plate under sinusoidal loading. This question type, which is one of the common examples in the literature, is available with various methods. Application engineers mostly use Microsoft Excel excel macro program, VBA, has written program codes for both finite element method and integration method. The difference between the results of these programs and the CPU time is calculated.
Keywords: Engineering; Mühendislik